2017
DOI: 10.1007/s00192-017-3322-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cognitive impairment in older women with pelvic floor disorders

Abstract: MCI and early dementia were prevalent in our population seeking care for PFDs. Women with cognitive impairment experienced worse condition-specific QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Moreover, the type and severity of dementia may affect the degree of UI [ 14 , 15 ]. In addition, a recent study showed that the prevalence of mild CI and dementia was 15% and 17%, respectively, in women over 55 years with pelvic organ dysfunction, including UI [ 16 ]. These findings imply that a close relationship exists between UI and cognitive function and that CI influences the occurrence of UI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the type and severity of dementia may affect the degree of UI [ 14 , 15 ]. In addition, a recent study showed that the prevalence of mild CI and dementia was 15% and 17%, respectively, in women over 55 years with pelvic organ dysfunction, including UI [ 16 ]. These findings imply that a close relationship exists between UI and cognitive function and that CI influences the occurrence of UI.…”
Section: Discussionmentioning
confidence: 99%